(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
This article analyses three poems from Tim Burton’s The Melancholy Death of Oyster Boy & Other Stories – Robot Boy, The Melancholy Death of Oyster Boy, and Mummy Boy – through the lenses of Gothic and monster theory. It contends that Burton crafts monstrous children whose bodies symbolise abjection, otherness, and cultural anxieties. Existing in liminal spaces – between human and non-human, living and dead, child and object – these figures disrupt familial and societal norms. Engaging with theorists such as Kristeva, Cohen, Georgieva, and Scahill, the article investigates how Burton’s child monsters serve as boundary-crossing entities that unveil the instability of identity, the brutality of normative frameworks, and the Gothic’s critique of the family. Rather than posing a threat, these children are themselves victims: silenced, ostracised, and ultimately obliterated, demonstrating that monstrosity is not an inherent quality but a manifestation of societal failure.